History of the School of Public Health at the Centre of Postgraduate Medical Education (1971 to 2021) - Janusz Ostrowski; Wojciech Stefan Zgliczyński; Jarosław Pinkas; Ryszard Gellert (Wiedza Medyczna, 2022)
The 50th anniversary of the Centre of Postgraduate Medical Education (CMKP) was celebrated in 2021. Since the beginning, the School of Public Health (SZP) has been inseparable linked with the CMKP. Throughout this period, the position of the SZP director has been held by eight persons i.e. Bogusław Kożusznik (1971 to 1977), Marek Sanecki (1978 to 1991), Andrzej Wojtczak (1991 to 1996), Jerzy Leowski (1996 to 2003), Janusz Opolski (2003 to 2004 and 2005 to 2011), Maria Miller (2005 to 2005), Dorota Cianciara (2011 to 2018) and Jarosław Pinkas (since 2018). In the paper, the consecutive directors and the SZP modifications during the period of the recent 50 years is presented.